Improved pharmacological properties of nitrotyrosine drug via fluorination: A theoretical study. (December 2020) - Zhang, Ying; Dong, Zhigui; Han, Jiao; Wei, Zhang
Graphical Abstract: Fluorination of anti- Alzheimer drug as promising strategy to improve pharmacological activity of drug. Highlights: The stability and electronic properties of pristine and fluorinated nitrotyrosine drug were studied. The results show that the electronic spectra of fluorinated derivatives exhibit a red shift toward higher wavelengths. Intramolecular hydrogen bonding of the drug were influenced by fluorination. Abstract: It has become obvious that fluorinated drugs have a significant role in medicinal applications. In this study, the fluorination of 3-nitrotyrosine as an anti-Parkinson and anti-Alzheimer drug was explored using density functional theory calculations. We have investigated the most important chemical properties of 3-nitrotyrosine that affect the pharmacological activity of the drug. We found that the intramolecular hydrogen bonding and intramolecular charge of the drug were influenced by fluorine substitution. Our results also reveal that the fluorination altered the stability, solubility, and molecular polarity of the 3-nitrotyrosine drug. The density of state analysis also determines sharp resonance states of fluorine atoms with the 3-nitrotyrosine drug states particularly in the highest molecular orbital reigns, suggesting hybridization of the fluorine states with the state of the drug. Moreover, our results show that the electronic spectra of fluorinated derivatives of 3-nitrotyrosine drug exhibit a red shift toward higher wavelengths (lower energies). Our calculations show that the free energy transfers of fluorinated derivatives of the 3-nitrotyrosine drug in water were negative that it meant that the designed molecules dissolving in aqueous phase occurred simultaneously. Consequently, the results of the present study show that the fluorination of 3-nitrotyrosine drug could be considered as a promising strategy to design useful drugs with better pharmacological properties.